Measurement of the real urbanization level in China and its international comparison. Issue 2 (2nd December 2019) - Cai, Jiming; Guonan, Du; Yuan, Liu
Abstract : Purpose: The purpose of this paper is to estimate the real urbanization level in China so as to provide a measurement that can be compared with the international level. Design/methodology/approach: Taking into consideration 300m residents living in the administrative towns (300m residents here are referred to the population in administrative towns, including those in all counties), the gap between the urbanization rate of China and that of the world average becomes much wider. Findings: China, however, implements the administrative system of government at the central, provincial, municipal, county and township levels. By city, it means the jurisdiction at and above the level of county, which includes the municipality directly under the central government, prefecture-level municipal and county. By town, it means the jurisdiction below the level of county (including the Chengguan Town, or capital town, where the county government is located) and exclusive of rural townships. Originality/value: China has witnessed rapid development for 40 years since the reform and opening up in 1978. Nowadays, China has already stepped into the period of post-industrialization, with its urbanization rate (UR) of permanent population reaching 58.58 percent. However, on the basis of registered population, the UR is 43.37 percent, which is not only far below the average level of 81.3 percent in high-income countries, but also lower than the average of 65.8 percent in upper middle-income countries which are comparable to China in terms of per capita income. (The classification of state income level is based on the data of national income per capita and division standards in 2016 from the World Bank, in which annual revenue per capita in high-income countries reaches over US$12, 736 and that in upper middle-income countries between US$4, 126 and US$12, 735.)